Minutes of the Meeting of the Special-Purpose Committee of the Expert Council of Rheumatology, Ministry of Health of the Russian Federation No. 15 dated October 24, 2015 - Article Editorial (Научно-практическая ревматология)
Minutes of the Meeting of the Special-Purpose Committee of the Expert Council of Rheumatology, Ministry of Health of the Russian Federation No. 15 dated October 24, 2015.